(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article examines the current state and prospects of development of commodity exchanges in Ukraine. Studied the stages of evolution and commodity exchanges of the wholesale market. The basic trends and patterns of domestic commodity exchanges. Analysis of scientific approaches leading scientists in this field. Detailed operations on commodity exchanges Ukraine and the main participants. The place and role of commodity exchanges in the national economy and outline promising targets for improving the functioning of commodity exchanges. It is established that the conclusion of business transactions on exchanges improves the economic benefit of business. The characteristic main problems of formation and functioning of commodity exchanges in Ukraine. Consider measures that must precede the introduction of futures and options contracts within the national commodity exchange market. DONE general conclusions about the main problems of the commodity exchange market of Ukraine. The main determinants of commodity exchanges, which are caused by the request of the national economy for creating commodity exchange market and globalization processes, which are actively involved in Ukraine. Proved that the most significant influence on the formation of a civilized market of commodity exchange must state by introducing legal and institutional mechanism for its functioning and development of appropriate national strategies. Determined dualistic nature of the further development of commodity exchanges in Ukraine that is due, as the need for qualitative changes of domestic commodity exchange market and the objective necessity of its integration into the global exchange space.